Intrinsic and extrinsic factors affecting the evolution of virulence in the HIV-associated opportunistic human fungal pathogen Cryptococcus neoformans - Yuanyuan Wang; Yiwu Yu; Jihong Liu; Linghua Li; Xiaoqing Chen; Sichu Xiong; Yuying Pan; Qinyu Tang; Munika Moses; Ping Zhan; Guojian Liao; Min Chen; et al. (Virulence)
The fungus Cryptococcus neoformans is considered the leading cause of mortality in immunocompromised patients. While extensive research has unveiled the molecular epidemiology of C. neoformans, the influence of genetic and environmental factors on genotype–phenotype correlations remains poorly understood. Specifically, it remains unclear whether the genetic and environmental variability observed across isolates from diverse sources has significant implications for the pathogen’s virulence. In this study, we analyzed 105 Chinese C. neoformans isolates, including 54 from HIV-infected patients, 44 from HIV-uninfected individuals and seven from a natural environment. Multilocus sequence typing (MLST) revealed that sequence type (ST) 5 predominates across all clinical isolates; however, genotypic diversity was notably higher in isolates from HIV-uninfected individuals and the natural environment, whereas HIV-infected isolates exhibited restricted genetic variation. Furthermore, isolates from HIV-uninfected individuals exhibited significantly enhanced virulence traits, including elevated capsule production, increased melanin production, improved survival in human cerebrospinal fluid (CSF), reduced phagocytic uptake, and higher mortality in both Galleria mellonella and murine models of cryptococcosis. Importantly, these pathogenic phenotypes were correlated with CD4+ T cell counts, highlighting the critical role of host immunity in shaping C. neoformans virulence. Whole-genome sequencing and genome-wide association studies (GWAS) further revealed that variations in genes involved in carbohydrate metabolism, such as CDA3 and GPD1, may drive host-specific virulence evolution. Our results support a genotype–phenotype correlation, demonstrating that both genetic and environmental factors shape the virulence of C. neoformans, with significant implications for understanding host–pathogen interactions and guiding therapeutic strategies.